Implementasi Sistem SCADA Proses Filtrasi pada Water Treatment Plant (WTP) Menggunakan PLC Siemens S7-1200 (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Water is an essential need for all living things on Earth to support various vital biological processes. Without water, life cannot exist because of its role as a solvent, nutrient transport medium, and temperature regulator. Water in nature does come from various sources such as rivers, lakes, rain, and groundwater, which are not all clear because they are contaminated with particles or other substances, in contrast to mountain springs which are often purer. In this study, a water filtration system was created aimed at making turbid water purify to be suitable for use by assessing the NTU (Nephelometric Turbidity Unit) of turbid water due to suspended particles such as mud or sediment, thus producing clear water suitable for use for household or irrigation purposes. The use of two Siemens S7-1200 PLCs as controllers in the water filtration system is a reliable redundant approach to automate mechanisms such as pump, valve, and NTU sensor settings. PLC 1 is used for the filtration system and PLC 2 is used for the water distribution system. The water distribution process uses a DC pump that runs when it receives input from the water level sensor in the raw water tank and clean water tank. The water filtration process has three main stages: reading the water turbidity level using a turbidity sensor, regulating the water flow rate using a solenoid valve, and filtering the water using filter media. The system's operation can be monitored and controlled through a SCADA system. Both PLCs are connected using an OPC server for communication between the PLC and SCADA. The OPC server sends data from the PLC to the Wonderware InTouch application as the SCADA system. To monitor and control the SCADA system, users must log in to access the system.